2020
DOI: 10.1080/23311932.2020.1809309
|View full text |Cite
|
Sign up to set email alerts
|

A review of the chemical composition, nutritional and health benefits of dates for their potential use in energy nutrition bars for athletes

Abstract: The purpose of this review was to provide information about the chemical composition and nutritional benefits of date fruits, known more commonly as dates. We also present the potential application of dates in energy nutrition bars for athletes. Dates have a high nutritional value and are rich in carbohydrates, dietary fibers, proteins, minerals, and many vitamins including B complex. Carbohydrates comprise 70% of dates mainly as fructose and glucose. In addition, dates are rich in calcium, iron, magnesium, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 36 publications
0
30
0
Order By: Relevance
“…Previous studies on dates have indicated that date fruit is a rich source of nutrients such as ash, fiber, and sugars, and is also low in protein and fat . [26,27] In contrast, spirulina is known to contain high amounts of protein and suitable amounts of high-quality oil [29] . Sugar contents indicated that the Sukkari puree contained higher amounts of total sugars and sucrose than the Khalas puree, whereas the latter contained higher amounts of glucose and fructose than the former.…”
Section: Chemical Properties Of Date Puree and Spirulina Powdermentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on dates have indicated that date fruit is a rich source of nutrients such as ash, fiber, and sugars, and is also low in protein and fat . [26,27] In contrast, spirulina is known to contain high amounts of protein and suitable amounts of high-quality oil [29] . Sugar contents indicated that the Sukkari puree contained higher amounts of total sugars and sucrose than the Khalas puree, whereas the latter contained higher amounts of glucose and fructose than the former.…”
Section: Chemical Properties Of Date Puree and Spirulina Powdermentioning
confidence: 99%
“…It is well known that dates are a richer source of vitamins than other dried fruits, and that fresh dates contain higher levels of vitamins than dry dates. This could be due to the fact that the drying process has a negative impact on vitamins [27,30,31]) . The vitamins B5, B6, B12, E, and K were only detected in spirulina and were not detected in the date puree.…”
Section: Vitamin and Mineral Contents Of Date Puree And Spirulina Powdermentioning
confidence: 99%
“…There are no available reports about the chemical composition of UBDF pulp which is also expected to differ depending on the processing or preparation method. The moisture, crude protein, lipid, ash, and total carbohydrate contents of Barhi fruits at the khalal maturity stage were reported as 83.2, 1.1, 0.1, 0.8, and 31.1%, respectively, on a fresh weight basis [ 38 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to these variables, regional variants vary. Unpollinated fruits yield little, inferior fruits with no kernel, unlike the one called “Shees.” These unpollinated, high-fiber fruits are termed “Alhashf.” This wastage fiber could be utilized in the food industry to modify the properties of dairy, meat, bread, and jam products [ 38 ]. UBDF is a unique source of dietary fiber to generate low-fat or high-fiber functional foods that benefit community health and SA palm producers.…”
Section: Introductionmentioning
confidence: 99%
“…Dates could be an alternative to add modifications to food bars and other snacks. This food bar has the potential to be marketed as a nutrient-rich food bar, ready-to-eat snacks, desserts, and helping food producers and processors think about diversifying other foods [8].…”
Section: Introductionmentioning
confidence: 99%